الخطاب السجالي في أدب محمود محمد شاكر - بني عامر، عاصم محمد أمين (الجامعة الإسلامية العالمية - مجمع البحوث الاسلامية, 2014)
This paper deals with polemical discourse in the literary works of Mahmud Muhammad Shakir, This is considered one of the most complex literary genres. Its difficultness comes from its being spontaneous with no prior plan. Shakir employed all means and mechanisms for effective communication and delivering the message to his audience. Through his polemical essays, written introductions and poems, he exhausted all available means to disseminate his polemical views. He made brilliant use of linguistic techniques and all other means available to him to put across his massage in defending the cause of Arabic language, Islamic creed and culture.
Keywords: شاكر، محمود محمد -- الأدب العربي -- النقد الأدبي